Journal of Prisoners on Prisons, V34, #1 - Piché, Justin (Université d'Ottawa | University of Ottawa, 2025)
VOLUME 34, Number 1 (2025) is a special issue of the Journal of Prisoners on Prisons on “Emotions and the Affective Politics of Incarceration” edited by Jennifer M. Kilty (University of Ottawa), Rachel Fayter (Carleton University) and Justin Piché (University of Ottawa). In addition to articles on the emotions, affect and imprisonment, this edition of the journal includes a call for contributions for the 50th edition of Prisoners’ Justice Day, book reviews, and artwork by Steel Door Studios (https://steeldoorstudios.com).
INTRODUCTION FROM THE ISSUE EDITORS Feeling the Carceral: Emotions and the Aff ective Politics of Incarceration Jennifer M. Kilty, Rachel Fayter and Justin Piché ARTICLES Emotional Perspectives from Carceral Spaces and Beyond Ronnice Giscombe, Wes Guzylak, Ogo Esenwah, Varina Gurdyal and Nadia Judunath Education, Gossip and Social Carcerality: Contesting the Liminal Spaces Between Incarcerated Body and Incarcerated Mind Billie Cates and Gerty B. À fl eur de peau: An In-depth Look at Two Strategies of Handling Emotion in French Prisons Y.E., Hannah Davis and H.W. The Power of Meaning Star Morrison A PAWSitive Connection Todd Ramsum Emotions Are Ours as Humans: The No Apology, Apology Cathee Prison is a Trap K WooDZ RESPONSE Carceral Power and Emotions: A Refl ection Kevin Walby PRISONERS’ STRUGGLES Call for Contributions: Commemorating the 50th Anniversary of Prisoners’ Justice Day Abolition Coalition BOOK REVIEWS The Sentences That Create Us: Crafting a Writer’s Life in Prison by Caits Meissner (2022) Chicago: Haymarket Books, 339 pp. Reviewed by David Morales Zenquis The Prisoner Society: Power, Adaptation and Social Life in an English Prison by Ben Crewe (2009) Oxford: Oxford University Press, 519 pp. Reviewed by Mohammad Jahirul Islam Out to Defend Ourselves: A History of Montreal’s First Haitian Street Gang by Maxime Aurélien and Ted Rutland (2023) Halifax: Fernwood Publishing, 170 pp. Reviewed by Sacha Alfonzo V Divide and Conquer: Race, Gangs, Identity and Conflict by Robert D. Weide (2022) Philadelphia: Temple University Press, 284 pp. Reviewed by Gary J. Kowaluk Available Titles and Call for Book Reviews Journal of Prisoners on Prisons UPCOMING SPECIAL ISSUES – CALL FOR CONTRIBUTIONS Profiling and Carceral States / Les profilages et les états carcéral Justin Piché and Sandra Lehalle / Observatoire des profi lages P4W 25 Years Later: Memory, Art and Action Linda Mussell, Rachel Fayter and Wendy Johanne Bariteau COVER ART “Blue Boy” (front cover) Steel Door Studios 2024 “Blue Boy 4” (back cover) Steel Door Studios 2024
Keywords: Jail; prisoner ethnography; prison writing; prison ethnography; carceral; penal; criminal justice; punishment; detainee; prisoner; detention; prison; penitentiary; incarceration; imprisonment